Concerns of Pregnant Women in “Prenatal Screening/Diagnosis” Practice and Termination of Pregnancy - Kasnakoglu, Berna Tari; Cakar, Mehmet; Okem, Zeynep Guldem; Tanacan, Atakan; Fadiloglu, Erdem; Orgul, Gokcen; Beksac, Mehmet Sinan (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Objective To investigate the reasons for decision-making and concerns of patients in the field of prenatal screening, invasive prenatal diagnostic testing (IPDT), and termination of pregnancy (TOP).Study Design This questionnaire-based study consisted of 107 pregnant women who were referred for prenatal screening to the Hacettepe University Hospital. The questionnaire given to patients was prepared from scratch since there is no standard set of questions measuring patients’ feelings and concerns regarding prenatal screening/diagnosis, IPDT, and TOP.Results Our questionnaire results showed that it is possible to classify decision-making factors into 6 groups: psychological, social, fear, religious/faith, support, and trust. The majority of patients were undecided (48.6%) about IPDT if prenatal screening test results were risky. Only 23.4% of patients were willing to accept IPDT. On the other hand, 55.1% of patients were not willing to undergo TOP if the fetal karyotyping results were abnormal. Religious factors seem to be important in refusing IPDT and TOP.Conclusion Physicians should re-evaluate their practice in the field of prenatal screening and diagnosis in light of the high refusal rates of IPDT and TOP. Understanding factors influencing womenʼs decision-making processes provides insight for service providers to help women at high risk of having foetal anomalies to make better-informed choices.
Keywords: antenatal care; pregnancy; prenatal diganostics